PELAYANAN KESEHATAN DI ERA JAMINAN KESEHATAN NASIONAL SEBAGAI PROGRAM BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN - Prima Maharani Putri; Patria Bayu Murdi (Universitas Slamet Riyadi, 2019)
The principle of justice, certainty and usefulness in BPJS services has not been felt by all parties, especially the Health Service Provider (PPK) as BPJS provider and also the BPJS who has no clear position and authority due to Law No. 40 of 2004 concerning the Social Security System National and Law No. 24 of 2011 concerning the Social Security Organizing Agency which collided with the Presidential Regulation on Health Insurance. Although the benefits of BPJS services have been felt mainly by BPJS Beneficiaries (PBI) participants, there are injustices and legal uncertainties and the possibility of triggering fraud in various parties, especially the PPK with the INA-CBGs system at the JKJ health service program.